Editorial endogamy in some Latin American dental journals - Aquino Canchari, Christian Renzo; Santivañez-Isla , Luis Arturo; Casimiro-Ramos, Johan Rafael; Huaman-Castillon, Katia Medalith (Brazilian Dental Science, 2023)
Objective: Scientific publication in a journal by a member of the editorial committee of the same journal is known as authorial endogamy. To determine the presence of authorial endogamy in some Latin American dental journals. Material and Methods: Observational, descriptive, retrospective study. Eight dental journals from Brazil, Cuba and Chile indexed to Scopus in the period of 2018 - 2021 were analyzed. An evaluation was made of the manuscripts that include a member of the editorial committee as author. The results were expressed in percentages and frequency measurements and for the bivariate analysis, the Mann-Whitney U test and Fisher’s exact test were used (p<0.05). Results: A total of 2026 articles, from which 14.52% (n=256), of authorial endogamy were found. The endogamy articles were mostly original articles 98.05% (n=252), experimental design 39.70% (n=102), advisory council 49.36% (n=153), co-authorship position 58.97% (n=184), with presence of 1 endogamic author per article 82.94% (n=214), the number of days from submission to acceptance were statistically lower in endogamic articles (p=0.003). Conclusion: The presence of editorial endogamy in some dental journals in Latin America was low, this finding is more frequent in original articles, mostly from the advisory board and as co-author. Additionally; it was found that endogamic articles took less days in editorial process. KEYWORDS Editorial policies; Ethics in scientific publication; Electronic journals; Latin America; Endogamy authoral (DeCS).